2009
DOI: 10.1177/0162243909337121
|View full text |Cite
|
Sign up to set email alerts
|

Buckets of Resistance: Standards and the Effectiveness of Citizen Science

Abstract: In light of arguments that citizen science has the potential to make environmental knowledge and policy more robust and democratic, this article inquires into the factors that shape the ability of citizen science to actually influence scientists and decision makers. Using the case of community-based air toxics monitoring with ‘‘buckets,’’ it argues that citizen science’s effectiveness is significantly influenced by standards and standardized practices. It demonstrates that, on one hand, standards serve a bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
286
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(292 citation statements)
references
References 29 publications
1
286
0
5
Order By: Relevance
“…Likewise, a bird-watcher may participate in a bird counting project to help protect wildlife. Citizens can also influence research projects so that they are more responsive to the needs of disadvantaged or marginalized groups (Epstein, 1998;Corburn, 2005;Ottinger, 2010).…”
Section: Benefits Of Citizen Sciencementioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, a bird-watcher may participate in a bird counting project to help protect wildlife. Citizens can also influence research projects so that they are more responsive to the needs of disadvantaged or marginalized groups (Epstein, 1998;Corburn, 2005;Ottinger, 2010).…”
Section: Benefits Of Citizen Sciencementioning
confidence: 99%
“…To collect air samples, the citizens used inexpensive, easy-to-use devices colloquially called ''buckets,'' whereas the Louisiana Department of Environmental Quality used more sophisticated ''Summa canisters.'' Many regulators expressed skepticism about whether the buckets provided sufficiently accurate data, but Ottinger (2010) reports that these concerns were partially alleviated because the air from the buckets was analyzed using the same standardized analytical technique used by regulators and industry. Another concern about the buckets was that they were used to collect short-term air samples, whereas state regulatory standards were based on average pollution levels over longer periods of time.…”
Section: Box 1 Data Quality and Integritymentioning
confidence: 99%
See 2 more Smart Citations
“…Hess (2016) argues that civil society organizations contend with the issue of undone science in a variety of ways, such as by identifying knowledge gaps and generating independent research to fill those gaps. Indeed, many STS scholars have demonstrated that civil society groups are capable of sophisticated levels of independent engagements with scientific research (Ottinger 2009;P. Brown 2007;Irwin 2002;McCormick 2009;Epstein 1996;Wynne 1996).…”
Section: Civic Informaticsmentioning
confidence: 99%